The Relationship between Emotional Intelligence, Personality Traits and Academic Achievement of University Students in Bangladesh - Siddique, Md. Nur-E-Alam; Mondal, Md. Abdul Hannan (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2025)
Introduction: Emotional intelligence (EI) and personality traits (PT) have an impact on academic achievement (AA) of university students. The purpose of this study was to explore the relationship and gender-based difference between EI, PT, and AA among university students. Method: This cross-sectional study involved 400 university students selected using a multistage random sampling technique. EI, PT, and AA were the primary variable of this study. The Bangla-translated Emotional Intelligence Scale (EIS) and the Bangla-adapted Ten Item Personality Inventory (TIPI) were used to evaluate the participants' emotional intelligence and personality traits. The AA was measured by participants’ academic result. Pearson correlation, independent sample t-test, and multiple regression analysis were used for this study purpose. Results: Among 400 students, 34% were male, and 66% were female. The mean age was 19.09 ± 2.80 and ranged from 17 to 26. Firstly, we found that AA was not significantly correlated with EI or five personality traits. However, EI was significantly associated with three personality traits, conscientiousness (r = 0.20, p<0.01), emotional stability (r = 0.23, p<0.01), and openness to experience (r = 0.28, p<0.01). Secondly, male students exhibited significantly higher EI compared to female students. Finally, EI and PT did not considerably influence the AA of the participants. Conclusions: Although EI and PT were correlated but does not guarantee higher AA because this correlation was not so strong or direct and complex interplay of other variables such as motivation and learning strategies. University authorities can utilize these findings to enhance students' academic performance.